The Phenomenon of Corruption and Efforts to Combat Corruption in Indonesia - La Ode Faiki (Jurnal Multidisiplin Madani, 2023)
Corruption that occurs in Indonesia is very worrying and has an extraordinary negative impact on almost all aspects of life. Corruption has destroyed the economic system, democratic system, political system, legal system, government system, and social order in this country. On the other hand, efforts to eradicate corruption that have been carried out so far have not shown optimal results. Corruption at various levels still occurs as if it has become a part of life and is even considered a normal thing. If this condition is allowed to continue, sooner or later corruption will destroy this country. Corruption has three phenomena which include: bribery, extortion, and nepotism. Corruption usually involves other parties, which contains fraud on public bodies or the general public, betrayal of trust, for self-interest, other people or entities that can harm the country's finances or the country's economy. The formulation classified as a criminal act of corruption today can be seen in Law Number. 31 of 1999 concerning the Eradication of Corruption; juncto (jo) Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes (UUPTPK). The birth of reform has determined corruption as the "enemy" together, in fact it is even more "rampant" with a more sophisticated modus operandi. Corruption is decentralized in various sectors of life and decentralized to the lowest level of life. At the national economic level, current government policies that have the most potential for corruption are political corruption by plundering BUMN assets and playing on contracts. Privatization carried out by the government so far is often not carried out in a transparent manner and there is no public accountability. This kind of pattern has the potential for deviation and has the potential to be misused for the benefit of a particular party or for the sake of maintaining a regime. Observing the phenomenon of corruption in our country as well as the causes of corruption and its impact in the form of suffering for the people, a determination arises that corruption must be eradicated. Once again, corruption must be eradicated